Chemical, physical and thermal characterization of wood pellets from different compositions - Camargo, Bruno Silva; Braghni Junior, Aldo; Camargo, Sâmique Araujo; Caraschi, José Cláudio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Pellets are characterized by renewable biomass and may be an option for replacing fossil fuels. The objective of this paper is to analyze and compare a set of pellets of different compositions, based on their physical, chemical and thermal characteristics for energy purposes, comparing them against international standards. To this end, the international standards SS187120 (Swedish), ONORM M7135 (Austrian), DIN 51731 (German) and the official standards recommended by the Pellets Fuel Institute (PFI) (United States) were used as reference for the parameters analyzed. Three types of pellets were analyzed: Pinus ssp. with 15% in mass of charcoal fines (P1), Pinus ssp. (P2) and Eucalyptus ssp. (P3). The analyses carried out indicated that the P1 pellets had the greatest higher heating value (20.52 MJ.kg-1). With regard to moisture content, mechanical durability and bulk density, all pellets achieved the quality parameters. Regarding the gaseous emissions of carbon monoxide (CO), some of the pellets presented values higher than the CONAMA standard. As for NOX emissions, they presented values below the standard and there were no emissions of SO2. Thus, it can be observed that the different types of pellets analyzed had a high energy potential according to the Austrian standard ONORM M7135.